Removal of an organic dye from water using a predispersed solvent extraction - Lee, DW; Hong, WH; Hwang, KY (MARCEL DEKKER INC, 2000)
The removal of Solvent Yellow 1 in a range from 0.25 to 10 ppm by weight from an aqueous solution using a predispersed solvent extraction (PDSE) was investigated and compared with conventional solvent extractions in batch mode. Colloidal liquid aphrons (CLAs) made out of kerosene were used as a predispersed organic solvent. To form CLAs. Tergitol 15-S-3 and sodium dodecylbenzene sulfonate were used as oil-soluble and water-soluble surfactants, respectively. The ratio of solvent volume to pregnant solution volume was less than 0.025. The efficiency of the extraction with CLAs can be higher than that of a single-staged conventional extraction process with a shorter contact time. The recovery of used CLAs with a colloidal gas aphrons (CGAs) flotation was measured using different surfactants. CLAs with an extremely large surface area can also reduce processing time and energy cost. PDSE is therefore a promising process for the removal of organic materials from water.